2020
DOI: 10.4103/jfmpc.jfmpc_137_20
|View full text |Cite
|
Sign up to set email alerts
|

CD4 cells count as a prognostic marker in HIV patients with comparative analysis of various studies in Asia Pacific region

Abstract: Purpose: To evaluate the correlation between CD4+ cells count with orofacial and systemic manifestations in newly diagnosed HIV seropositive patients and comparison of results with the previous studies. Materials and Methods: Hundred (100; 57 males and 43 females) newly diagnosed HIV seropositive patients, before starting antiretroviral therapy (ART) were included in the study. These patients were clustered according to CD4+ cells count into three groups: 0–200 cells/mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…During HIV infection, HIV damages the host immune system by inducing CD4 cell apoptosis, eventually leading to immunodeficiency and opportunistic infections. [11,12] CD4 cell counts in HIV patients are closely related to disease progression. [11][12][13] However, in newly diagnosed PLWH, CD4 cell counts are often lower than normal at the time of diagnosis, and the degree of decline in CD4 cell counts is often associated with a delay in diagnosis.…”
Section: This Study Was Supported By the "Ningbo Science And Technolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…During HIV infection, HIV damages the host immune system by inducing CD4 cell apoptosis, eventually leading to immunodeficiency and opportunistic infections. [11,12] CD4 cell counts in HIV patients are closely related to disease progression. [11][12][13] However, in newly diagnosed PLWH, CD4 cell counts are often lower than normal at the time of diagnosis, and the degree of decline in CD4 cell counts is often associated with a delay in diagnosis.…”
Section: This Study Was Supported By the "Ningbo Science And Technolo...mentioning
confidence: 99%
“…[11,12] CD4 cell counts in HIV patients are closely related to disease progression. [11][12][13] However, in newly diagnosed PLWH, CD4 cell counts are often lower than normal at the time of diagnosis, and the degree of decline in CD4 cell counts is often associated with a delay in diagnosis. [14] Delayed diagnosis of HIV means an increased risk of opportunistic infections and a corresponding reduction in survival time.…”
Section: This Study Was Supported By the "Ningbo Science And Technolo...mentioning
confidence: 99%
“…Despite the availability of effective treatments, only 67% of people living with HIV have access to Antiretroviral Therapy (ART) 1 . HIV infection results in a reduction in CD4+ T lymphocyte counts, interfering in the immune system leading to greater susceptibility of opportunistic infections and neoplastic processes 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported differences in the prevalence of oral manifestations associated with HIV infection 5 , 7 , 10 , 11 . The prevalence of oral lesions could be influenced by the development of the country, demographic locality, healthcare system, medicine availability, HIV strains, stage of HIV, deleterious habits, and gender 3 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%